Load distribution on the foot and lofstrand crutches of amputee football players - KARAGÖZOĞLU, CENGİZ; ŞANLI, GÖKTUĞ; ÇOTUK, HASAN BİROL; GÜLMEZ, İRFAN; GERÇEK, NEJLA; RAMAZANOĞLU, NUSRET; UZUN, SELDA; TATAR, YAŞAR (ELSEVIER IRELAND LTD, 2018)
Background: Amputee football is a worldwide popular sport with positive physical and psychological effects on the disabled. Amputee players use their hands dominantly for locomotion. However, the effect of using upper extremity which is not accommodated to loading is not very well known. Research question: The objective of this study was to determine the load distribution of amputee football players during walking, running and kicking the ball. Methods: This study was conducted with 15 certified amputee football players (age 24.5 +/- 5.8 years, body weight 62.3 +/- 10.9 kg, height 171.6 +/- 7.7 cm). The loads on their non-amputated lower extremity were measured with F-Scan mobile system sensors inserted in their shoes, and the loads on their upper extremities were measured with F-Grip system sensors affixed to the gloves. The participants were asked to walk, run and kick the ball using Lofstrand Crutches. Results: The maximum loading on the upper extremities during walking, running and kicking the ball varied between 111% and 175% of the body weight. While loading during walking and running was similar, the loading on the upper extremity during kicking the ball exceeded that of walking by 58.1% and running by 47.4%. The maximum loading on the non-amputated lower extremity varied between 134% and 196% of the body weight. Loading during running was 46.2% higher than that of walking. The loading on the foot during kicking the ball was 45.7% higher than that of walking. The loading on the foot during running and kicking were similar. Significance: Walking-running-kicking the ball with LC resulted in unusual loading particularly on the upper extremity. During running, the increased loading was transferred to the foot rather than the hands. During kicking, the loading increased extremely and was mainly transferred to the hands. The frequent repetition of kicking during the game may therefore increase the incidence of upper extremity injuries.
Keywords: Amputee football; Lofstrand crutche; Loading; Kicking; GROUND REACTION FORCES; PRESSURE DISTRIBUTION; AXILLARY CRUTCHES; ASSISTED-GAIT; AMBULATION; DYNAMICS; WALKING; CHILDREN